Returnee entrepreneurship in China: the multi-faced story in the travel of location, time and culture - Xu, Zimu (Springer, 2022)
With experience, knowledge and skills accumulated in both home and host countries, returnee entrepreneurs have been recognised as the international knowledge brokers and make significant contributions to the countries’ social-economic development. Particularly, China has emerged as an important context for its high number of global mobility of citizens, the rapid development of the economy, various policies initiatives designed to attract returnees, and the national effort in high-tech industries (Gruenhagen et al., Foundations and Trends in Entrepreneurship 16:310–392, 2020). With China’s rapid economic growth and accelerated global integration, there is a shifting perspective and reality of entrepreneurs returning from overseas. They face various challenges rising from their physical travel of locations, experiencing and adjusting to multi-cultures, as well as changes brought by time moving forward. This chapter discusses the changing nature and current challenges and opportunities.
Keywords: China; Entrepreneurship; Time; Culture; Returnees